Concordância dos escores de risco cardiovascular em indivíduos infectados pelo HIV e HCV - Librelotto, Paula Rubin Facco (2016)
The Acquired Immunodeficiency Syndrome (AIDS) caused by the human immunodeficiency virus (HIV) is a serious, emergent, pandemic disease, considered of the biggest problems in the world. The introduction of Highly Active Antirretroviral Therapy (HAART) allowed immune deficiency reduction caused by the virus, decrease morbidity associated with AIDS and, consequently, the increased life expectancy. The aging of this population has been accompanied by high cardiovascular risk, and the mechanisms responsible for this increase are not entirely clear. It is believed that chronic inflammation generated by the HIV virus and hepatitis C virus (HCV), the metabolic changes related to the viruses and antiretroviral therapy are related to the cardiovascular morbidity and mortality. Knowing the cardiovascular risk of these patients through the use of clinical risk scores is important in order to plan possible interventions which can reduce the risks. This transversal study evaluated the prevalence of cardiovascular risk in 128 patients divided into three groups: 52 patients with monoinfected by HIV, 33 subjects with monoinfection by HCV, 33 subjects coinfected by HIV / HCV, at the University Hospital of Santa Maria - Brazil. For that, different clinical risk scores were applied: the Framingham Risk Score (FRS), the Reynolds Risk Score (RRS) and Global Risk Score (GRS). We evaluated the concordance and correlation between the methods and the percentage of patients who were reclassified after the application of different scores. The prevalence of cardiovascular risk among all the populations studied was 8.7% for FRS, 4.3% for RRS and 48.1% for GRS. HCV patients showed higher risk prevalence when compared to other patients. FRS classified more patients as low risk in all population subgroups, suggesting that it is a score that underestimates the risk for HIV and HCV populations. At our study, 9.6% of HIV monoinfected population had moderate to high risk according to FRS, while 50% had moderate to high risk of the GRS, showing that depending on the method used to assessment the risk, patients are reclassified, which implies in different measures and prevention interventions. The risk scores were weak concordance and correlation with each other, independent of the evaluated subgroup. This study emphasizes the need to establish specific risk scores for the HIV population.